Alantolactone promotes ER stress‐mediated apoptosis by inhibition of TrxR1 in triple‐negative breast cancer cell lines and in a mouse model. Issue 3 (4th January 2019) - Yin, Changtian; Dai, Xuanxuan; Huang, Xiangjie; Zhu, Wangyu; Chen, Xi; Zhou, Qiulin; Wang, Canwei; Zhao, Chengguang; Zou, Peng; Liang, Guang; Rajamanickam, Vinothkumar; Wang, Ouchen; et al.
Abstract: Triple‐negative breast cancer (TNBC) is a subtype of breast cancer with poor clinical outcome and currently no effective targeted therapies are available. Alantolactone (ATL), a sesquiterpene lactone, has been shown to have potential anti‐tumour activity against various cancer cells. However, the underlying mechanism and therapeutic effect of ATL in the TNBC are largely unknown. In the present study, we found that ATL suppresses TNBC cell viability by reactive oxygen species (ROS) accumulation and subsequent ROS‐dependent endoplasmic reticulum (ER) stress both in vitro and in vivo. Thioredoxin reductase 1 (TrxR1) expression and activity of were significantly up‐regulated in the TNBC tissue specimens compare to the normal adjacent tissues. Further analyses showed that ATL inhibits the activity of TrxR1 both in vitro and in vivo in TNBC and knockdown of TrxR1 in TNBC cells sensitized ATL‐induced cell apoptosis and ROS increase. These results will provide pre‐clinical evidences that ATL could be a potential therapeutic agent against TNBC by promoting ROS‐ER stress‐mediated apoptosis through partly targeting TrxR1.